Perilaku Pemustaka Dalam Pemanfaatan Perpustakaan UIN Sunan Ampel Di Masa New Normal - Supriyatno, Hary (Universitas Negeri Padang, 2022)
New normal is a transition from pandemic to normal. This transition period certainly has an impact on the behavior of users in using the library, due to the culture of using digital media in meeting information needs during the pandemic. The condition that occurred in the UIN Sunan Ampel library was no exception. This study aims to determine the level of visits and borrowing as well as user behavior during the new normal period. Based on the results of research using descriptive qualitative methods with a sample of one hundred respondents, it shows a tendency that the frequency of visits is once a week with a duration of one hour. The need for a visit is to complete lecture assignments and read collections. In terms of discipline and user compliance with rules and regulations, it is still relatively high, namely, by always carrying and scanning KTM when entering. The collection services that are most in demand are General and Reference. Meanwhile, in terms of procedures for browsing collections, the majority of users choose to go straight to the shelves.